1979
DOI: 10.1111/j.1532-5415.1979.tb06030.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hormonal Activities Relative to the Severity of Essential Hypertension

Abstract: Endocrine activity in patients with essential hypertension was studied by measuring the urinary excretion of catecholamines, prostaglandin E (PGE) and cyclic adenosine monophosphate (cAMP). Simultaneously, plasma renin activity, concentrations of serum sodium, potassium, blood urea nitrogen (BUN) and creatinine were determined. Systolic blood pressure and BUN increased progressively with age until the sixth decade. Urinary excretion of norepinephrine was correlated with the systolic blood pressure. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…In comparison with the subjects in other studies (5, 12), most of our patients undoubtedly were ingesting an excess amount of salt, as judged by the urinary excretion of NaCl. Despite this deviation, a number of aspects were comparable to those previously reported (4, 13, 14). First, systolic and diastolic blood pressures increased progressively with age (13).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In comparison with the subjects in other studies (5, 12), most of our patients undoubtedly were ingesting an excess amount of salt, as judged by the urinary excretion of NaCl. Despite this deviation, a number of aspects were comparable to those previously reported (4, 13, 14). First, systolic and diastolic blood pressures increased progressively with age (13).…”
Section: Discussionsupporting
confidence: 87%
“…Although plasma renin activity is not a reliable criterion for the prediction of thiazide effectiveness, it is still a matter of theoretical interest to evaluate the physiologic role of renin activity in patients with essential hypertension. In a recent study (14), we again found that plasma renin activity decreased progressively with age. Yet, in the patients of this study, plasma renin activity seemed also to be governed by the salt intake.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our previous studies (4, 5) have shown that a number of endocrine changes are associated with the severity of essential hypertension. Since the blood pressure increases progressively with the increase of relative body weight, it may be hypothesized that the weight increase results in changes of endocrine activities.…”
Section: Discussionmentioning
confidence: 96%
“…Despite these accumulated evidences, it is not known why overweight is associated with a high incidence of hypertension or why weight reduction favors a decreased incidence of hypertension. Our previous studies (4, 5) repeatedly showed a number of aspects of endocrine activities associated with the severity of essential hypertension. In order to throw some light on the relation between blood pressure and obesity, a population study was made in Kijimadaira village, Nagano‐ken, Japan.…”
mentioning
confidence: 89%